THE IMPORTANCE OF HUMANIZED CARE FOR WOMEN WHO ARE BALD DUE TO MEDICAL OR TRAUMATIC FACTORS: EMPATHY, WELCOMING PRACTICES, AND PROFESSIONAL ETHICS IN THE BEAUTY SECTOR - Chagas, Jhenifer Monique Ku's Schmitt (Revista Sistemática, 2022)
Hair loss in women resulting from medical treatments or traumatic events represents a profound transformation that extends beyond physical appearance, affecting identity, emotional well-being, and social interaction. In this context, the role of the beauty sector transcends aesthetic intervention and assumes ethical and psychosocial significance. This article examines the importance of humanized care for women who are bald due to medical or traumatic factors, emphasizing empathy, welcoming practices, and professional ethics as central pillars of responsible beauty services. Drawing on interdisciplinary academic literature from psychology, healthcare, and service ethics, the discussion highlights how empathic communication, individualized attention, and ethical conduct contribute to emotional safety, dignity, and empowerment. The analysis underscores the need for professional training that integrates emotional intelligence, cultural humility, and ethical awareness, positioning beauty environments as supportive spaces capable of fostering resilience and self-esteem. Ultimately, the article argues that humanized care is not an optional enhancement but a fundamental ethical obligation within the beauty sector when serving women experiencing hair loss.